Textile Collage as the Artistic Method to Comprehend Industrial Memory: the Analysis of the Project вЂњRadiant CityвЂќ by Elena Sharganova - Evgeniya Andreevna Golman (Интеракция. Интервью. Интерпретация)
The article is focused on the sociological analysis of the project “Radiant city” of Elena Sharganova, resident of the tenth season of Open Studios at the Center of Contemporary Art Winzavod (2023/24), that is devoted to the artist’s hometown — Nelidovo — and consists of a series of textile collages, made with mixed media techniques including photo printing, cyanotype, machine seam, hand embroidery. Sociological conceptualization of the project is made based on the interview with the artist, analysis of archive publications kindly provided by the artist, and researches on social memory and industrial cities. Based on the interpretation of collages as spaces of representation in terms of Henri Lefebvre that represent a zone of experience, in which images and symbols fill in physical space and knowledge about it, the article shows that the “Radiant city” is the artist’s reflections on Nelidovo’s unrealized development trajectories and destinies of small industrial cities in general. There are three key topics raised by the artist in this project: disappointment in communism and nostalgia for the past, the problem of small industrial cities’ development, interrelation of collective and individual memory. Elena Sharganova’s project significance is defined by experiments with art mediums and a research approach that brings together art and social issues.